2011
DOI: 10.1161/circoutcomes.110.959551
|View full text |Cite
|
Sign up to set email alerts
|

Guideline-Discordant Periprocedural Interruptions in Warfarin Therapy

Abstract: Background-Periprocedural interruptions in warfarin therapy increase thromboembolic risks to patients and are not indicated for all procedures. We sought to determine the frequency and guideline concordance of periprocedural warfarin interruptions to inform a future educational intervention. Methods and Results-In October and November of 2009, an anonymous postal survey was sent to all patients followed for more than 1 year by the University of Michigan Anticoagulation service. Patients were asked how many tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…It has been reported that 50% of people on VKA therapy undergo invasive procedures at least once during the first year of treatment [1] and up to 11% of those taking antiplatelet agents for coronary stents require surgery within 2 years of stenting [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that 50% of people on VKA therapy undergo invasive procedures at least once during the first year of treatment [1] and up to 11% of those taking antiplatelet agents for coronary stents require surgery within 2 years of stenting [2].…”
Section: Discussionmentioning
confidence: 99%
“…frequently encountered in general surgery [1,2]. Given the high risk of intra-and postoperative bleeding, the management of these patients may involve the temporary interruption of such medications and, especially in the case of vitamin K antagonists (VKAs), perioperative replacing with short-acting anticoagulants, such as ultrafractioned heparin (UFH) or low-molecular-weight heparin (LMWH).…”
mentioning
confidence: 99%
“…This study also demonstrated the feasibility of dental treatment performed for stroke inpatients undergoing rehabilitation. It was suspected that many subjects were in need of special care during dental treatment because of underlying diseases and prescribed medications. This means that dentists treating stroke patients must be aware of the therapeutic regimes relevant to stroke and other possible complications, including hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Each year, approximately 20% to 50% of patients with AF are directed to temporarily interrupt anticoagulant therapy for an elective procedure. 8,9 In the RE-LY trial, 25% of patients in each treatment arm had an interruption of therapy at least once for an invasive procedure. 10 Data from ROCKET-AF and ARISTOTLE show rates of temporary interruption of approximately 33% in each trial, again emphasizing how common this clinical scenario is likely to be in day-to-day practice.…”
Section: A New Era Of Anticoagulantsmentioning
confidence: 99%